2018
DOI: 10.1002/slct.201702721
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Catalytic Reduction of 4‐Nitrophenol by MOFs‐Derived N‐Doped Carbon

Abstract: With the development of Metal organic frameworks (MOFs) materials, various functional carbon materials prepared using MOFs as precursors have attracted more and more attention. In this work, the N‐doped carbon nanomaterial N‐C have been synthesized by annealing of ZIF‐8. In the reduction of p‐nitrophenol which is one of the most prevalent organic pollutants, N‐C shows good activity, great stability, reusability and minimal pollution compared with some of the previously metallic catalysts. The N‐C prepared by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…[19] In Freire's study, the N-containing groups were pyridinic > pyrrolic > N-quaternary (N-graphitic) � N-oxide, and the S-containing groups were mainly thiophene-like (thiophenic aromatic CÀ SÀ C structure). Although the exact nature of the active sites in such systems was not clearly identified, some works have demonstrated the importance of pyridinic [39] and graphitic [14] N-groups in N-CNT, and thiophenic or sulfoxide groups in S-CNT. [15] Additionally, the presence of hydrophilic groups on CNT surface can improve their dispersion in water, which is important for this catalytic reaction.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…[19] In Freire's study, the N-containing groups were pyridinic > pyrrolic > N-quaternary (N-graphitic) � N-oxide, and the S-containing groups were mainly thiophene-like (thiophenic aromatic CÀ SÀ C structure). Although the exact nature of the active sites in such systems was not clearly identified, some works have demonstrated the importance of pyridinic [39] and graphitic [14] N-groups in N-CNT, and thiophenic or sulfoxide groups in S-CNT. [15] Additionally, the presence of hydrophilic groups on CNT surface can improve their dispersion in water, which is important for this catalytic reaction.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…10,11 The MOF-derived nanoparticles by calcination still have a porous structure and exhibit high electrical conductivity with excellent electron transport behavior due to the doping of nitrogen atoms, which could promote electrocatalysis. 12 Oxygen reduction reaction (ORR) indicated that better catalytic performance could be achieved by MOF derivatives than by precious metal Pt/C catalysts. 13 Besides, the metal ions and organic ligands in MOFs are linked by coordination bonds and these relatively weak chemical bonds may break under proper conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The observed rate constant and activity factor values are better than those of the reported nonmetallic catalysts. 29,37…”
Section: Resultsmentioning
confidence: 99%